New marine algal records from Arabian Gulf coastline of Kuwait: DOI: 10.48129/kjs.12675 - Al-Hasan , Redha; Mohammed, Fatemah (Kuwait Journal of Science, 2022)
During 2014-2016 a project was launched to update and examine the current status of five phyla of benthic marine algae, in addition to epiphytic diatoms and marine Tracheophyta thriving along the coastal area of Kuwait. 173 species of algae were collected and identified. Fourteen new records of algal species for Kuwait including 2 species as new records from the Arabian Gulf are here reported for the first time. These species are assigned to the Chlorophyta (4), Ochrophyta (1), Rhodophyta (5) and Cyanobacteria (4). From Kuwait coastal line one species of marine angiosperm is also found for the first time. Five algal species collected from Kuwait coastal line remain unidentified.